اسلام کا قانونِ اسیرانِ جنگ : مولانا مودودی کے موقف کا تحقیقی جائزہ: Islamic Law and Prisoners of War: A Study of Mawlana Mawdudi’s Point of View - Ali, Murad (FIKR-O NAZAR فکر ونظر, 2020)
This article aims to discuss the Islamic laws related to prisoners of war (POWs) in the writings of Mawl┐n┐ Mawd┴d┘. Islamic law pertaining to prisoners of war has remained one of the contentious issues for decades. Modern international law on protection of POWs is regarded as contrary, on various aspects, to Islamic law. Although, both frameworks have many overlaps, but there is fundamental difference in their source of origin. Many Muslims have been attempting to reconcile Islamic law on POWs with modern international law without considering the fundamental incompatibilities among the two legal frameworks. In addition, some have opined that the Qur’┐n mentions only two ways of dealing with POWs: mann (freedom gratis) and fid┐’ (ransom) (Qur’┐n 47: 4) and that execution and enslavement have been strictly prohibited by Islamic law. Moreover, prohibition of execution is also wrongfully attributed to Mawd┴d┘. It will be argued in this paper that this opinion is not so insightful and is in fact distorting the variegated Islamic legal tradition. The article also argues that this attribution to Mawd┴d┘ is flimsy. Finally, the paper presents Mawd┴d┘’s discourse on POWs.